(untitled) (International Journal of Medical and Surgical Sciences, 2015)
A better understanding of sperm physiology and the development of new methods for assessment of this function, opens the possibility of improving both new IVF techniques including cytoplasmic sperm injection (ICSI) and making more accurate diagnoses. Implementing new therapies, allowing treatment at the cellular level. recovering or improving sperm function that is altered, eventually generated Molecular Andrology. This radical change to assess fertility in men has varied the definition of the Andrology Clinic to incorporate these concepts. Defining the Andrologist, as a physician who, in addition to the clinical aspects of male infertility, is a specialist in the evaluation and treatment of sperm defects. The tests conducted by the Andrologist determine not only the biological aspects of sperm from testicular production level, but also their functional attributes and fertilizing capacity.